Crucial questions about the kingdom of God : the sixth annual mid-year lectures of 1952 delivered at Western Conservative Baptist Theological Seminary of Portland, Oregon - Ladd, George Eldon, 1911-1982 (W. B. Eerdmans Pub. Co, 1952)
For the purposes of publication, each lecture has been divided into two chapters. With the exception of the last two chapters, the study is centered in our Lord's teachings, for the kingdom of God is one of the most central themes in his Evangel. It will appear to many to be a weakness that so little appeal is made to the Old Testament prophecies; but I am convinced that we must interpret the Old Testament by the New and not vice versa, and this procedure has been deliberately followed. - Author's foreword.